Phenotype-based screening of selected trees with medicinal properties for inhibition of the Wnt/B-catenin signaling pathway using zebrafish (Danio rerio) as a model - Fabile, Ramon Camelo A.; Fuentes, Rolly G. (2016)
The Wnt signaling pathway is an evolutionarily conserved pathway that plays crucial roles during embryonic development; however, aberrant activation of the pathway has been found to affect the progression of diseases and various cancers. Therefore, discovery of possible sources for new inhibitors that target different components of the pathway is essential in creating combination therapies that can manage these diseases. A phenotype-based screening of selected medicinal trees using zebrafish (Danio rerio) as a model was thus conducted. Embryos at sphere stage (4.3 hpf) were exposed to 300 mM LiCl, causing the expression of the eyeless phenotype in zebrafish. Lithium-treated embryos were then exposed to 50 and 100 ug/mL plant extract at 30% epiboly (4.7 hpf). At prim-6 stage (24 hpf), return of eye development in embryos were noted along with developmental defects at long pec stage (48 hpf). Results of the screen revealed presence of Wnt inhibitors in crude methanolic extracts of Mangifera indica, Cinnamomum mercadoi, Azadirachta indica and Syzygium polycephaloides. The screen also detected high toxicity from Tabebuia avellanedae. Among the positive candidates, S. polycephaloides showed the best inhibitory activity showing no toxicity at 50 ug/mL and slight toxicity at 100 ug/mL. At both concentrations, owever, S. polycephaloides showed toxic effects on zebrafish embryo resulting in obvious developmental defects such as heart edema and bent tail. Presence of catechins, quercetin, gallic acid and syzygiol in methanolic extracts of this species may contribute to its inhibitory activity. Further studies on isolation, purification and characterization of the active compounds are recommended.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and technology